Chromium deposition and poisoning of LSCF and LSM oxygen electrodes of solid oxide electrolysis cells - Chen, K.; Bo, W.; Hyodo, J.; Ishihara, T.; Jiang, San Ping (Electrochemical Society Inc., 2015)
The degradation of solid oxide electrolysis cells (SOECs) is an issue of both scientific and technical importance. In this study, chromium deposition and poisoning at La0.6Sr0.4Co0.2Fe0.8O3-d (LSCF) and La0.8Sr0.2MnO3+d (LSM) oxygen electrodes are studied under SOEC operation conditions at 800 oC. Performance degradation was observed for the reaction in the presence of Fe-Cr alloy metallic interconnect. The results indicate the deposition of SrCrO4, CrO2.5 and Cr2O3 phases on the surface of LSCF oxygen electrodes and YSZ electrolyte surface and on the LSM electrode inner surface. Cr deposition is closely related to the increased segregation of SrO species under anodic polarization conditions.